Myasthenic Crisis Care Up to Date - William Stevenson (Jurnal Kedokteran Meditek, 2016)
AbstrakMiastenia crisis merupakan komplikasi dari myasthenia gravis ditandai dengan memburuknya kelemahan otot dan dapat mengakibatkan kegagalan pernapasan yang mengancam kehidupan. Airway, Breathing and Circulation life support sangat penting dalam manajemen krisis miastenia disamping pemberian obat-obatan. Pasien dengan miasthenia crisis umumnya memerlukan perawatan di ICU. Artikel ini memberikan update mengenai tatalaksana miasthenia crisis .1 Kata kunci : krisis miasthenic, kegagalan pernafasan, life support, ICU AbstractMyasthenia crisis is a complication of myasthenia gravis is characterized by a worsening of muscle weakness and can lead to life-threatening respiratory failure. Airway, Breathing and Circulation as life support is very important in myasthenic crisis management in addition to the provision of medicines Patients  with  miasthenia  crisis  generally  require  treatment  in  the  ICU. This  article provides an update on the treatment of myasthenia crisis1 Keywords : myasthenic crisis, lifethreatening-respiratory failure, life support, ICU